(3QSGdI GdJbQjY hGdHjGf hEbGeI GdMLI dhdi GdReGf hEjVGM GdeMLI def CaGA Edi GdJhMjO hGdEjeGfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdefRg Yf GdYOO hJhSdJ Edjg Hhdjg GdbGFe Ydi cd faS HeG cSHJ s
(3BNQgG (B:s
(3cGf Pdc bdI GdCeGfGJ hcKQ GdSH hGdbPa dCgd GdOjfGJ hUGQ GdOjf eYjQI dCgdg Je GdJbQjY hGdHjGf Hefg ehdGfG hJaVd bGFe GdReGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B62s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds